Dermatofibrosarcoma protuberans diagnosed by a single biopsy - Kristian Bakke Arvesen; Carsten Sauer Mikkelsen; Torben Steiniche; Birgitte Stausbøl-Grøn (PAGEPress Publications, 2012)
This brief report is about a 9 year old girl presenting with a 2.5 cm circular blue to violet discoloration on the anterolateral upper left thigh. The first biopsy taken revealed the diagnosis dermatofibrosarcoma protuberans. The patient underwent surgery at a specialized sarcoma center with post operative histology showing free wide resection margin. Preoperative chest x-ray showed no sign of metastasis. This brief report emphasizes the significance of the use of biopsy when cutaneous elements look suspicious and diagnosis is unclear.